Rethinking diabetes : what science reveals about diet, insulin, and successful treatments - Taubes, Gary (Alfred A. Knopf, 2024)
"An eye-opening, comprehensive history of diabetes research and treatment, by award-winning journalist and the best-selling author of Why We Get Fat"--